Analisis Pengukuran Tingkat Kematangan Aplikasi E-Commerce Menggunakan COBIT 4.1 - Muhammad Hamka; Feri Wibowo (JUITA : Jurnal Informatika, 2015)
One kind of information technology for SMEs to expand business networks and marketing is an e-Commerce. Benefits and actual maturity level of IT management becomes a benchmark towards the development and utilization of e-commerce strategies for SMEs. The purpose of this study was to assess the position of Etsa Luhur SMEs related implementation of e-commerce and targets to be achieved in the future in the use of e-commerce. Results of the assessment of the level of maturity (maturity level) position of IT management today (existing). The next will be determined targets for each IT process maturity was elected to serve as a guide for a group of SMEs etching Sublime in the use of  IT. Assessment of the level of maturity using the domain Plan and Organise (PO). Domain PO cover includes strategies to determine the direction of development of ICT best support the achievement of business goals. Results of the assessment related to the maturity level of IT development strategy at the level of 0 (0.499), which is non-existent. It means that Etsa Luhur SMEs does not have a concern for IT management as well. Towards the development of ICT in Etsa Luhur SMEs expected to reach level 3, which is Defined Proces